Antecedents of Green Awareness for Eco-Friendly Products - Alamsyah, Doni Purnama; Muhammed, Hayder Alhadey Ahmed (UI Scholars Hub, 2021)
Manuscript type: Empirical Research Research Aims: This study examined factors that support the cultivation of green awareness among customers for the improved consumption of eco-friendly products Design/methodology/approach: The examination was conducted through an analysis of customer behaviors as they relate to green advertising, green brand attributes, perceived value of green initiatives, and green brand image. To this end, a survey was administered to 500 customers of Supermarket Retail, which is an establishment in West Java Province that offers eco-friendly products Research Findings: The findings indicated that the variable that most strongly supports the development of green awareness is green advertising, followed by the perceived value of green initiatives, green brand image, and green brand attributes. Theoretical Contribution/Originality: The research provides practical contributions by formulating recommendations for industries that offer eco-friendly goods and encouraging the pursuit of healthy lifestyles, particularly in Indonesia, through the consumption of eco-friendly products. Practitioner/Policy Implication: This finding obviously becomes separating suggestion for an industry that moves on the eco-friendly product, with puts green advertising for the product through their some criterion. Research limitation/Implications: There are still several customer behaviors that are based on marketing strategy conducted by the company like green brand preference. Furthermore, this study does not discuss the research model that relates to customer’s demography